CURPH Interview 458 with a 1956 Hungarian Refugee: 37 Years Old, Male, Chief accountant - Columbia University School of International Affairs
Transcript of an interview conducted as part of the Columbia University Research Project on Hungary (CURPH) in the wake of the 1956 Hungarian Revolution. Place of Interview: Vienna (Austria) Date of Interview: July 1957 Interview ID: 458 Interview Type: B Covers topics related to everyday life and politics in Hungary between the end of World War II and the 1956 Hungarian Revolution. The document notes that the interviewee had the following characteristics: Education level: University Occupation: Chief accountant Religious preference: Roman Catholic Place of residence before emigration: Budapest Date of departure: 1 January 1957